SERUM TUMOR-NECROSIS-FACTOR LEVELS IN ACUTE MYOCARDIAL-INFARCTION AND UNSTABLE ANGINA-PECTORIS - (:unkn) unknown (WESTMINSTER PUBL INC, 1993)
Tumor necrosis factor (TNF) enhances leukocyte adherence to vascular endothelium and increases procoagulant activity in the endothelial cells. Thus it may be implicated in the pathogenesis of acute vascular occlusions. To study the role of TNF in the early stages of acute myocardial infarction (MI), the authors measured circulating TNF levels in the sera of patients with acute MI and unstable angina pectoris. Blood samples were obtained within six hours after onset of chest pain and stored at -70 degrees until tested. A sensitive sandwich enzyme-linked immunosorbent assay (ELISA) test was used for TNF measurement. C-reactive protein (CRP) levels were determined semiquantitatively. Immediate complications such as heart failure, arrhythmia, and shock were also noted. Twenty-four patients with electrocardiographically and biochemically confirmed acute MI and 14 patients with unstable angina pectoris were included in the study. TNF levels were serially assessed at the time of admission and at hours 6, 24, 48, 72, and 96 after onset of chest pain in 2 patients with acute MI. Detectable TNF was found in 13 sera of the acute MI group (range; 10-1510 pg/mL) and 4 sera of the angina pectoris group (range; 15-240 pg/mL). There was no correlation between the serum TNF levels and the occurrence of complications and the extent of myocardial damage. CRP response was unrelated to TNF levels. Contrary to previous reports, serial measurement of TNF revealed that peak values were reached within six hours and disappeared after twenty-four hours. The authors concluded that TNF may contribute to the development of acute coronary artery occlusion by changing vascular endothelial cell characteristics instead of being a late consequence of myocardial infarction.
Keywords: CORONARY-ARTERY LESIONS; FACTOR-ALPHA CACHECTIN; SMOOTH-MUSCLE CELLS; ENDOTHELIAL-CELLS; INTERLEUKIN-1; PATHOGENESIS; DISEASE